Shopee Analysis And The MSME Revolution Pushing The Indonesian Economy Into The Digital Era - Putri, Ressi Anugrah; Astarani, Juanda (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
In the digital era, e-commerce platforms like Shopee are key drivers of Indonesia's economic transformation, particularly for MSMEs. This research analyzes Shopee's impact on MSME development in Indonesia. Using a combination of primary and secondary data, 200 MSMEs that actively use Shopee were sampled purposively. The results show that Shopee significantly enhances market access, operational efficiency, digital literacy, and customer satisfaction. This underscores the need for steps such as improving digital infrastructure and fostering collaboration between the government, private sector, and educational institutions. In conclusion, Shopee plays a crucial role in revolutionizing MSMEs and pushing Indonesia towards a more digital economy.